A single institutional retrospective evaluation for younger patients with primary central nervous lymphomas on a modified R-MPV regimen followed by radiotherapy and high dose cytarabine - Hattori, Keiichiro (J Clin Exp Hematop, 2017)
We conducted a retrospective analysis of patients younger than 60 years (N = 10, median age 54.5) with newly diagnosed primary central nervous system lymphoma (PCNSL) at the University of Tsukuba Hospital from January 2008 to November 2016. All the patients were scheduled to receive a single regimen without registration to any clinical trials. This was based on a phase 2 study by Memorial Sloan-Kettering Cancer Center (MSKCC); induction chemotherapy with rituximab, methotrexate, procarbazine, and vincristine (R-MPV) (five to seven cycles), followed by whole-brain radiotherapy (rd-WBRT) (23.4 Gy) and two high-dose cytarabine (HD-AC) cycles as a consolidation. The median age was 54.5 years, and median follow up duration was 33.1 months. The 3-year overall survival (OS) and progression-free survival (PFS) were 69% (95% CI 31–89%) and 56% (95% CI 20–81%). The median OS and PFS were not reached, respectively. Acute and delayed toxicities were manageable. In particular, OS and PFS of seven patients who achieved CR by the R-MPV induction chemotherapy were signiﬁcantly superb (3-year OS, 100%; 3-year PFS, 80%), implying that a large proportion of patients in CR after the completion of this treatment may achieve durable disease control. On the other hand, all of the three patients who had progressive disease during this treatment died of disease progression within 1 year after diagnosis without achieving CR. Identifying the patients having a risk of failure in the R-MPV induction chemotherapy is important, and may allow us to consider a potentially more effective regimen.